Relación de la traumatología forense en casos de heridas por arma de fuego en atención primaria en salud - Ojeda Flor, Priscilla Elizabeth (Machala : Universidad Técnica de Machala, 2022)
ABSTRACT Introduction: Forensic Traumatology is the science that describes or studies the injuries caused to a body with the same body of another person or with an object that may be a firearm; injuries are any aggression or damage caused to part or all of a person's or animal's body by an object, animal, person, part of the body or by deprivation of a vital element. Objective: To establish the relationship of forensic traumatology in cases of firearm injuries through a bibliographic review for the correct approach in primary health care. Methodology: The study is carried out in a retrospective descriptive manner through a bibliographic review in the scientific bases of SCIELO, EBSCO, PUBMED, MESH, with information available from 2017 to the present for the extraction of qualitative information, compiling information on the relationship of traumatology in medicolegal cases. Conclusion: Forensic traumatology is a field of legal medicine that involves everything about the injuries that a person can have, due to different types of weapons. In firearms it is essential to recognize with which weapon the act was perpetrated, according to this, it will be possible to recognize the injuries caused, taking into account how the events have occurred. Keywords: forensic traumatology, gunshot wound, legal medicine, lesionology.
Introducción: La Traumatología forense es la ciencia que describe o estudia las lesiones provocadas a un cuerpo con el mismo cuerpo de otra persona o con un objeto que puede tratarse de un arma de fuego; las lesiones son toda agresión o daño provocado a una parte o el todo de un cuerpo de persona o animal por un objeto, animal, persona, parte del cuerpo o por privación de elemento vital. Objetivo: Establecer la relación de la traumatología forense ante casos de heridas por arma de fuego mediante de una revisión bibliográfica para el correcto abordaje en atención primaria en salud. Metodología: El estudio es realizado de manera descriptiva retrospectiva a través de una revisión bibliográfica en las bases científicas de SCIELO, EBSCO, PUBMED, MESH, con información disponible desde 2017 hasta la actualidad para extracción de información cualitativa recopilando información de la relación de la traumatología en casos medico legales. Conclusión: La traumatología forense es un campo de la medicina legal que involucra todo acerca de las lesiones que una persona puede llegar a tener, debido a diferentes tipos de armas. En las armas de fuego es indispensable reconocer de cual arma se ha perpetrado el hecho, de acuerdo a esto, se van a poder reconocer las lesiones ocasionadas, tomando en cuenta como han sucedido los acontecimientos.
Keywords: TRAUMATOLOGÍA FORENSE; HERIDA POR ARMA DE FUEGO; MEDICINA LEGAL; LESIONOLOGIA.